Effects Density and Salinity of Artificial Brackish Water on the Growth and Physiological Perfomance of Whiteleg Shrimp (Litopenaeus vannamei Boone, 1931) - Harri Ganda Prawira; Rustadi Rustadi; Susilo Budi Priyono (Universitas Gadjah Mada, 2023)
The increase in shrimp culture causes problems with the quality of seawater which is a source of water for whiteleg shrimp culture it self. The use of artificial brackish water as a culture medium is an effort to increase the availability of water sources for whiteleg shrimp culture. This study aims to (1) determine the optimum stocking density of whiteleg shrimp culture using artificial brackish water salinity based on carrying capacity, (2) determine mineral content (Mg, Ca, Na and K) in artificial brackish water, (3) study the effect of salinity on the growth and blood glucose concentration of whiteleg shrimp cultivated in artificial brackish water, (4) examine the effect of salinity on hemolymph osmolarity of whiteleg shrimp cultivated in artificial brackish water. This study used an experimental method consisting of two stages. Each stage was arranged using a completely randomized design (CRD). Obtained stocking densities of SD-50% (20 shrimps/50L), SD (40 shrimps/50L) and SD+50% (60 shrimps/50L). The best growth and performance were obtained in the treatment of 20 individuals, namely survival (SR) 87%, specific growth rate (SGR) 3.26%/day and hemolymph glucose concentration of 30.73 mg/dl. In the next stage of the research, the salinity treatments tested were seawater, 10 ppt, 15 ppt, 20 ppt and 25 ppt. The best shrimp performance was obtained in treatment 20 shrimps/50 L, namely survival rate 70.00%, specific growth rate (SGR) 1.55%/day, feed conversion ratio (FCR) 1.72, glucose haemolymp 73.44 mg/dl. The optimal osmotic work level (OWL) value is obtained at a salinity of 15-20 ppt.